Cultural Ritual Turned Sex Tourism: The Case of the Larap Slambu Ritual at Mount Kemukus in Central Java - Setiawati, R (KnE Social Sciences, 2018)
This study seeks to understand the Larap Slambu cultural event as a cultural tourist attraction at Mount Kemukus while exploring its rituals routed in the mixed concepts of belief, religion and myth prevalent in ancient Javanese communities referred to as Kejawen. A ritual as a habitual action contains transcendental values. Thus, rituals associated with voluntary performances by a community can be hereditary and characterized by a patterned behavior. This study uses a qualitative approach with the interpretive paradigm of ethnography method of communication. The findings reveal that the Larap Slambu, as a ritual commemorating the Javanese New Year (Malam Suro), is being used as a cultural tourism attraction featuring rituals in commemoration of Prince Samudro, an ancient Javanese prince, at his tomb and through puppet shows. Rituals performed are determined by a belief system adhered to by each ritual participant. Larap Slambu rituals can build social solidarity and togetherness through the ‘slamatan’ event, a form of gratitude for the blessings that have been received by ritual participants. Over the recent years, with an increase of tourists to the cultural site, sex rituals feature more. Keywords: ritual communication, communication ethnography, Larap Slambu, cultural attraction